Magnetic domains and domain wall pinning in atomically thin CrBr3 revealed by nanoscale imaging - Qi-Chao Sun (Nature Portfolio, 2021)
Van der Waals (vdW) magnets have allowed researchers to explore the two dimensional limit of magnetisation; however experimental challenges have hindered analysis of magnetic domains. Here, using an NV centre based probe, the authors analyse the nature of magnetic domains in the vdW magnet, CrBr3.